ANALYSIS OF LAND SUITABILITY FOR CINNAMON (CINNAMOMUN BURMANII) IN SUB-DISTRICT BATIPUH, TANAH DATAR REGENCY - Tira Mutiara; widya Prarikeslan (JURNAL BUANA, 2026)
This research was conducted in Batipuh Subdistrict, Tanah Datar Regency, aiming to determine the characteristics of the land and the level of land suitability of cinnamon. The method used for the analysis of land characteristics is a descriptive method and for the analysis of the level of land suitability using the matching method with the limiting factor approach. This research was conducted in accordance with the land evaluation guidelines for semi-detailed land analysis. The research variables are soil, climate and topography with indicators based on the Center for Research and Development of Land Resources. The results of this study indicate that Batipuh District has a temperature of 150C - 270C, a dominant rainfall of 2000-2500 mm per year and a high topography which is dominated by a slope class >15% because it is in the Bukit Barisan trail, and the soil conditions are suitable for growing cinnamon. The land suitability level of cinnamon in Batipuh District based on the limiting factor approach has various suitability classes, namely very suitable (S1) of 33.72%, suitable (S2) of 33.02%, marginally suitable (S3) of 30.2 % and 2.2% does not fit. The limiting factors in S3 and N are rainfall, soil depth, and drainage.